71.1k views
2 votes
Y= 2x – 15y = 5x Solve the system by using the substitution method

1 Answer

4 votes

Substituting the second equation in the first one, we get:


5x=2x-15.

Subtracting 2x from the above equation we get:


\begin{gathered} 5x-2x=2x-15-2x, \\ 3x=-15. \end{gathered}

Dividing by 3, we get:


\begin{gathered} (3x)/(3)=-(15)/(3), \\ x=-5. \end{gathered}

Substituting the above result in the second equation of the system, we get:


\begin{gathered} y=5\cdot(-5), \\ y=-25. \end{gathered}

Answer:


\begin{gathered} x=-5, \\ y=-25. \end{gathered}

User Mkimmet
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.